(untitled) - Rasulov, Sh.M.; Matnazarova, G.S; Abdukakharova, M.F. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: to study the epidemiological features of echinococcosis and improve preventive measures. Material and methods: official reports of the Centers of state sanitary and epidemiological surveillance of the Republic of Uzbekistan on echinococcosis in 2003-2017 and maps of registered epidemiological observations of patients were studied. The work uses epidemiological and statistical methods of research. Results: current anti-epidemic measures aimed at combating echinococcosis are not effective enough. This is clearly evidenced by the incidence of echinococcosis among the population of the country, which often turns into a chronic form, causes various complications and disabilities. Conclusions: echinococcosis is transmitted mainly by contact and household means. The incidence is recorded throughout the year. Infection occurs mainly from dogs and poorly washed greens. These epidemiological features should be taken into account when carrying out preventive measures.